THE COMPLEX STRATIGRAPHY OF THE HIGHLAND CRUST IN THE SERENITATIS REGION OF THE MOON INFERRED FROM MINERAL FRAGMENT CHEMISTRY - Ryder G.; Norman M.D.; Taylor G.J. (My University, 1997)
Large impact basins are natural drill holes into the Moon, and their ejecta carries unique information about the rock types and stratigraphy of the lunar crust. We have conducted an electron microprobe study of mineral fragments in the poikilitic melt breccias collected from the Taurus Mountains at the Apollo 17 landing site. These breccias are virtually unanimously agreed to be impact melt produced in the Serenitatis impact event. They contain lithic fragments and much more abundant mineral fragments of crustal origin. We have made precise microprobe analyses of minor element abundances in fragments of olivine, pyroxene, and plagioclase to provide new information on the possible source rocks and the crustal stratigraphy in the Serenitatis region. These data were also intended to elucidate the nature of the cryptic geochemical component in breccias such as these with low-K Fra Mauro basalt compositions. We chose the finest-grained (i.e., most rapidly quenched) breccias for study, to avoid reacted and partly assimilated fragments as much as possible.Most of the mineral fragments appear to have been derived from rocks that would fall into the pristine igneous Mg-suite as represented by lithic fragments in the Apollo collection, or reasonable extensions of it. Gabbroic rocks were more abundant in the target stratigraphy than is apparent from the Apollo sample collection. Some pyroxene and plagioclase, but probably not much olivine, could be derived from feldspathic granulites, which are metamorphosed polymict breccias. Some mineral fragments are from previously unknown rocks. These include highly magnesian olivines (up to Fo94), possibly volcanic in origin, that exacerbate the difficulty in explaining highly magnesian rocks in the lunar crust. It appears that some part of the lunar interior has an mg*[= 100 x Mg/(Mg/Fe) atomic] greater than the conventional bulk Moon value of 80-84. Other volcanic rocks, including mare basalts, and rapidly-cooled impact melt rocks do not contribute significantly to the fragment population. Nor do ferroan anorthosites contribute more than a tiny part of even the plagioclase fragment population. A few mineral fragments that are consistent with the cryptic low-K Fra Mauro chemical component were found, and these appear to be from gabbroic sources. The mineral fragment populations cannot be mixed in their observed proportions to produce the whole rock composition, because the fragments are more refractory and deficient in Ti, P, and alkalis. A preferential contribution to the melt from a rock similar to sodic ferrogabbro can partly resolve the discrepancy.The population of mineral fragments requires a very diverse population of igenous rocks that are not all related to each other, demonstrating the existence of a complex crust built of numerous separate igneous plutons. Many of these plutons may have crystallized at shallow depths. The chemical composition of the melt breccias, in combination with the mineral fragment data and an understanding of the cratering process, suggests that the deepest crust sampled by the Serenitatis impact (not necessarily the deepest crust) was basaltic in composition, including KREEP and gabbroic rocks like sodic ferrogabbro, and lacking abundant olivine-rich material. These were overlain by Mg-suite rocks of varied types, including norites and troctolites that supplied most of the olivine mineral fragments. Granulites, which are metamorphosed and more feldspathic breccias, were abundant near the surface. Remote sensing indicates that the entire Serenitatis region lacks ferroan anorthosite, consistent with the results of our study.